1977
DOI: 10.1111/j.1365-2362.1977.tb01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the degradation of lipoprotein‐X

Abstract: Abstract. Three patients suffering from prolonged obstructive jaundice were studied after surgical removal of biliary obstruction. Four days after surgery the initial cholesterol esterification rate in the plasma rose from very low activities to values three to four times higher than those found in normal subjects. During this time lipoprotein‐X decreased in concentration. The initial cholesterol esterification rate returned to normal values when plasma lipids and lipoproteins reached normal levels. During in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In control experiments in which lipoprotein lipase was omitted from the incubation mixture, the VLDL contained the full range of subfractions as observed with normal plasma (13). The median Sf value for our substrate VLDL was about 100, and more than 95% of the VLDL exhibited So values between 60 and 400 (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In control experiments in which lipoprotein lipase was omitted from the incubation mixture, the VLDL contained the full range of subfractions as observed with normal plasma (13). The median Sf value for our substrate VLDL was about 100, and more than 95% of the VLDL exhibited So values between 60 and 400 (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…For all iodination experiments, the molar ratio of iodine to apoprotein was less than 0. (13). Ultracentrifugation was performed with a Beckman L2-65B ultracentrifuge and a Beckman Ti-14 rotor at 42,000 rpm for 45 min at 14'C.…”
Section: Methodsmentioning
confidence: 99%
“…1 A and B should approximate that of VLDL, the major triglyceride pool in fasting plasma. These values are slightly less than that of VLDL, which is typically between 0.6 and 0.9, with an average value being 0.8 (38,39). The slight difference between the measured ratio for LDL and the observed value for VLDL may be due to intrinsic differences in the affinities of LDL and VLDL for triglyceride and cholesterol ester (40).…”
Section: Discussionmentioning
confidence: 98%
“…We demonstrated that HDL 2 -like particles could be produced from HDL 3 by incubation of normal plasma in the absence of lipoprotein lipase activity. 31 This interconversion was increased in the presence of LP-X, 32 a source of free cholesterol and phosphatidyl choline, and could be inhibited by p-OH mercuribenzoate, suggesting that HDL 3 -HDL 2 conversion was mediated by LCAT. 31 However, LCAT activity was found to be normal in hyperalphalipoproteinemia, 78 implying that LCAT-mediated conversion of HDL 3 to HDL 2 may be quantitatively of minor importance in hyperalphalipoproteinemia.…”
Section: Discussionmentioning
confidence: 98%